Implementation of Abortion Regulations on Medical Emergency Indications in Hospitals Based on Legal Aspects - ., Asmariah; Rochman, Dadang (KnE Social Sciences, 2023)
Abortion is one method to prevent unwanted births. This method was born along with the development of human life with various reasons and considerations, both legal and medical considerations. Abortion is a crucial law in health law. But abortion for several medical reasons is a legal way to provide solutions to safety problems related to pregnancy. As the executors of the abortion act, namely medical personnel who are closely related to existing regulations or policies, it is still a pro and contra polemic. Therefore, it is necessary to do an analysis to determine the clarity of the legality of the implementation of abortion on indications of medical emergencies in hospitals associated with abortion law regulations. The research design used in this study is qualitative through a descriptive analysis approach related to the legality issue of abortion regulations indicating medical emergencies between the Health Act and the Abortion Criminal Code. The sample in this study was an obstetrician with a medical team, namely midwives who worked in the delivery room. This study aims to determine the factors that influence the implementation of abortion regulations based on indications of medical emergencies in hospitals, specifically referring to Health Law No. 36 of 2009 with the Criminal Code on abortion. The factors that influence the implementation of abortion in hospitals are: the discovery of indicators or triggers that an abortion must be carried out in accordance with the Health Law Number 36 of 2009; it must be carried out as soon as possible because it endangers the patient’s life; carried out according to health standards and applicable laws; and the approval of both the parties to carry out official and legal abortion procedures and mechanisms according to legal and applicable rules. Based on this, abortions with indications of medical emergencies are often carried out in hospitals and can be justified by the principle of legitime defense. Legal issues regarding the regulation of abortion indicative of a medical emergency, as long as they refer to the procedures according to the Health Law, the legal issue of the Criminal Code cannot be brought to the surface, because abortion on the indication of a medical emergency is a medical action that must be carried out. Keywords: abortion, health law, hospital